Criteria for evaluation of clinical efficacy of anticancer medicines - A. V. Tikhomirova (Регуляторные исследования и экспертиза лекарственных средств)
Criteria for evaluation of clinical efficacy make it possible to assess the risk-benefit ratio of anticancer medicines that patients receive, in particular, for the treatment of solid malignant tumors. A medicine’s efficacy is assessed using special criteria called the endpoints of clinical efficacy, allowing most objective assessment of study results. It was demonstrated that nowadays clinical efficacy of anticancer drugs is assessed using «patient-centered» (overall survival and quality of life) and «tumor-centered» (response to therapy, progression-free survival, disease-free survival) endpoints. «Patient-centered» endpoints make it possible to evaluate the direct clinical benefit of chemotherapy in patients, while «tumor-centered» endpoints allow for evaluation of efficacy at earlier stages, without directly reflecting the clinical benefit. The analysis of the most suitable endpoints with the aim of making them interchangeable with the primary outcome measure – overall survival – is becoming more and more relevant in oncology. The choice of criteria of efficacy should be made taking into account the specific features of a particular oncological disease, study population and duration of therapy. The authors of the study analysed Russian and foreign literary sources containing information on criteria of efficacy of anticancer medicines and highlighted the advantages and disadvantages of these criteria. The study showed that clinical endpoints should be clinically significant, sensitive to therapy, easy to measure and interpret. It was demonstrated that comprehensive evaluation of outcome measures makes it possible to adequately assess the risk-benefit ratio of anticancer medicines.